628. Pharmacokinetics, Safety and Tolerability of Co-administration of Nacubactam and β-lactams after Multiple Doses in Japanese Healthy Subjects. (4th December 2021) - Sato, Hiroki; Morita, Jun; Miura, Tatsuo; Sumiya, Masayo; Takaya, Risako; Kondo, Kenichiro
Abstract: Background: Increase of carbapenem-resistant Enterobacterales (CRE) is a serious problem in the clinical setting and drugs which can treat patients with CRE are still limited. Nacubactam (OP0595) is a novel diazabicyclooctane-type β-lactamase inhibitor and being developed as a standalone drug to be co-administered with cefepime or aztreonam. Methods: A randomized, double-blind multiple dose study of nacubactam in co-administration with cefepime (Cohort 1) or aztreonam (Cohort 2) in Japanese healthy subjects was performed to assess pharmacokinetics, safety, and tolerability of co-administrations of nacubactam and cefepime or aztreonam. In each cohort, 6 subjects received 2 g of nacubactam and 2 g of concomitant drug (cefepime or aztreonam) and 2 subjects received placebo (saline) intravenously over 60 minutes, three times daily every 8 hours for 7 days. Plasma samples were collected and concentrations of each drug were analyzed by liquid chromatography-mass spectrometry (LC-MS/MS). Safety and tolerability assessments included treatment-emergent adverse events (TEAEs) and the evaluation of changes from baseline in safety laboratory test results, 12-lead electrocardiograms (ECGs), vital signs, and physical examinations. Results: Profiles of Cmax, tmax, AUC0-8, AUC0-∞ and t1/2 for nacubactam, cefepime and aztreonam are summarized in Table 1. Summary of Ctrough for nacubactam, cefepime and aztreonam are summarized in Table 2. Plasma concentrations of nacubactam, cefepime and aztreonam reached the steady-state by Day 4, and the mean accumulation ratios of Cmax and AUC0-8 on Day 7 to those of Day 1 were in the range of 0.91 to 1.10. As for the safety, no serious adverse event was observed in this study. There was 1 TEAE (seborrhoeic dermatitis) leading to the discontinuation in 1 subject in nacubactam/cefepime group, but it was judged as "Not related to study drug". Table 1. PK profiles of nacubactam and concomitant drugs on Day 1 and Day 7 Table 2. Summary of Ctrough of nacubactam and concomitant drugs Conclusion: In conclusion, no remarkable change in pharmacokinetics was observed in each drug with multiple concomitant administration for 7 days and safety and tolerability of co-administrations of nacubactam and cefepime or aztreonam were confirmed. Based on these results, nacubactam is currently under further development. Disclosures: All Authors : No reported disclosures